2019
DOI: 10.1093/jac/dkz302
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fungal activity of a novel triazole, PC1244, against emerging azole-resistant Aspergillus fumigatus and other species of Aspergillus

Abstract: Objectives The growing emergence of azole-resistant Aspergillus fumigatus strains worldwide is a major concern for current systemic antifungal treatment. Here we report antifungal activities of a novel inhaled triazole, PC1244, against a collection of multi-azole-resistant A. fumigatus strains. Methods MICs of PC1244 were determined for A. fumigatus carrying TR34/L98H (n = 81), TR46/Y121F/T289A (n = 24), M220 (n = 6), G54 (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…45 More recently, PC1244 has shown activity against azole-resistant A fumigatus. 46 In addition, an early phase randomized controlled trial (RCT) of PUR1900, a dry powder itraconazole preparation has shown good safety and tolerability, higher lung and lower plasma concentration compared with oral treatment. 47 Identifying children who may benefit from these treatments for inclusion in clinical trials would be an important clinical advance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 More recently, PC1244 has shown activity against azole-resistant A fumigatus. 46 In addition, an early phase randomized controlled trial (RCT) of PUR1900, a dry powder itraconazole preparation has shown good safety and tolerability, higher lung and lower plasma concentration compared with oral treatment. 47 Identifying children who may benefit from these treatments for inclusion in clinical trials would be an important clinical advance.…”
Section: Discussionmentioning
confidence: 99%
“…The long‐acting inhaled azole PC945, a potent inhibitor of A fumigatus , may provide a targeted approach in the lung 45 . More recently, PC1244 has shown activity against azole‐resistant A fumigatus 46 . In addition, an early phase randomized controlled trial (RCT) of PUR1900, a dry powder itraconazole preparation has shown good safety and tolerability, higher lung and lower plasma concentration compared with oral treatment 47 .…”
Section: Discussionmentioning
confidence: 99%
“…are the frequent focus of drug development. Recent reviews examine the available systemic antifungal drugs [ 7 , 12 , 13 , 14 , 15 , 16 ]. Thirteen new molecules include four in Phase 3 clinical trials [ 12 ].…”
Section: Need For New Antifungal Agentsmentioning
confidence: 99%
“…1,2,4-triazoles are the subject of extensive investigations because of their various clinical, industrial, and agricultural applications. Triazoles are bestowed with extensive biological activities including antibacterial [17][18][19], anti-fungal [20], anti-viral [21][22], anti-cancer [23][24][25], anti-microbial, anti-tumour and cytotoxic activities [26][27]. Their biological applications are generally found to be related with their oxidation potential [28] that entails the transfer of a hydrogen atom through a proton coupled electron transfer reaction.…”
Section: Introductionmentioning
confidence: 99%